The Use of Computed Tomography as a Teaching Resource for the Teaching of Structural Concrete in the Degree of Civil Engineering - Dorys C. González; Jesús Mínguez; Miguel A. Vicente (MDPI AG, 2021)
This paper shows a teaching experience related to the use of computed tomography in the teaching of concrete for undergraduate students of the civil engineering degree. This experience reveals that computed tomography is a powerful tool to facilitate the understanding of all those aspects related to the microstructure of concrete, thus facilitating comprehension of the correlation between the microstructure and its macroscopic response. In addition, students showed a greater motivation and interest in the subject, which promotes better academic learning. A pilot test was carried out to evaluate the viability of these practices and to analyze the teaching impact of this activity. The results show that students were very interested in the use of new technologies in teaching and, more particularly, in the use of computed tomography. The students satisfactorily received the project. A greater motivation of the students in the subject was also observed, which resulted in better grades when compared with those of previous courses. The results reveal that the average grade of the students rose by around 8%, and a higher percentage of students achieved higher scores when compared to the previous five years.